2001
DOI: 10.1359/jbmr.2001.16.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Stimulates In Vitro Osteoblast Differentiation and Creates a Favorable Template for Bone Tissue Formation

Abstract: In this study, we have investigated the behavior of fetal rat osteoblasts cultured on bioactive glasses with 55 wt% silica content (55S) and on a bioinert glass (60S) used either in the form of granules or in the form of disks. In the presence of Bioglass granules (55 wt% silica content), phase contrast microscopy permitted step-by-step visualization of the formation of bone nodules in contact with the particles. Ultrastructural observations of undecalcified sections revealed the presence of an electron-dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
2
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 21 publications
7
73
2
5
Order By: Relevance
“…Numerous studies demonstrated a positive effect of bioactive glasses on attachment, proliferation, differentiation and mineralization of bone cells compared to nonreactive surfaces (Vrouwenvelder et al 1992;Loty et al, 2001). However, in our study, no significant differences in the mRNA expression were found.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Numerous studies demonstrated a positive effect of bioactive glasses on attachment, proliferation, differentiation and mineralization of bone cells compared to nonreactive surfaces (Vrouwenvelder et al 1992;Loty et al, 2001). However, in our study, no significant differences in the mRNA expression were found.…”
Section: Discussioncontrasting
confidence: 76%
“…Because of these limitations the search for new alternative strategies for repairing bone defects have been focused on tissue engineering. One of its approaches is the use of material matrices as tem-plates for tissue growth in vitro (Loty et al 2001;ElGhannam et al, 1995;Ducheyne et al, 1994). Once again, bioactive glasses seem to find their place, for they fulfill most of the criteria required for a suitable scaffold to support bone tissue growth, since they are known to enhance proliferation and prevent de-differentiation of osteoblast in vitro (Price et al, 1997;El-Ghannam et al, 1997a,b;Vrouwenvelder et al, 1992;Matsuda and Davies, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive materials seem to provide a good scaffold to support osteoblasts. 4 When grafted to the defective bone areas, these bioactive scaffolds will not only stimulate osteoblast production, but as these materials are also biodegradable they should eventually be substituted by newlyproduced bone. 5 Studies have already shown that calcium oxide-silicon dioxide (CaO-SiO 2 )-containing materials, such as bioactive glass, 6 possess excellent bioactivity.…”
Section: Z Qiu H Yang J Wu Et Almentioning
confidence: 99%
“…Indeed, numerous in vivo and in vitro studies have shown that 45S5 Bioglass ® can stimulate bone regeneration (Bosetti et al 2003;Gough et al 2004;Livingston et al 2002;Loty et al 2001;Tsigkou et al 2007;Xynos et al 2000). As a result, Bioglass ® is said to be both osteoproductive and osteoconductive.…”
Section: Introductionmentioning
confidence: 99%